Detection of TP53 mutations in tissue or liquid rebiopsies at progression identifies ALK+ lung cancer patients with poor survival - Christopoulos, Petros; Dietz, Steffen; Kirchner, Martina; Volckmar, Anna-Lena; Endris, Volker; Neumann, Olaf; Heußel, Claus Peter; Herth, Felix; Eichhorn, Martin E.; Meister, Michael; Budczies, Jan; Allgäuer, Michael; et al. (Cancers, 2019)
Anaplastic lymphoma kinase (ALK) sequencing can identify resistance mechanisms and guide next-line therapy in ALK+ non-small-cell lung cancer (NSCLC), but the clinical significance of other rebiopsy findings remains unclear. We analysed all stage-IV ALK+ NSCLC patients with longitudinally assessable TP53 status treated in our institutions (n = 62). Patients with TP53 mutations at baseline (TP53mutbas, n = 23) had worse overall survival (OS) than patients with initially wild-type tumours (TP53wtbas, n = 39, 44 vs. 62 months in median, p = 0.018). Within the generally favourable TP53wtbas group, detection of TP53 mutations at progression defined a “converted” subgroup (TP53mutconv, n = 9) with inferior OS, similar to that of TP53mutbas and shorter than that of patients remaining TP53 wild-type (TP53wtprogr, 45 vs. 94 months, p = 0.043). Progression-free survival (PFS) under treatment with tyrosine kinase inhibitors (TKI) for TP53mutconv was comparable to that of TP53mutbas and also shorter than that of TP53wtprogr cases (5 and 8 vs. 13 months, p = 0.0039). Fewer TP53wtprogr than TP53mutbas or TP53mutconv cases presented with metastatic disease at diagnosis (67% vs. 91% or 100%, p < 0.05). Thus, acquisition of TP53 mutations at progression is associated with more aggressive disease, shorter TKI responses and inferior OS in ALK+ NSCLC, comparable to primary TP53 mutated cases.
Gesehen am 26.06.2019
Im Titel ist das Zeichen "+" hochgestellt